1999
DOI: 10.1162/105474699566035
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Proprioceptive and Visual Feedback on Geographical Orientation in Virtual Environments

Abstract: To effectively use a virtual environment (VE) for applications such as training and design evaluation, a good sense of orientation is needed in the VE. “Natural” human geographical orientation, when moving around in the world, relies on visual as well as proprioceptive feedback. However, the present navigation metaphors that are used to move around in the VE often lack proprioceptive feedback. To investigate the possible consequences this may have, an experiment was conducted on the relative contributions of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
72
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 18 publications
12
72
3
Order By: Relevance
“…Whereas previous studies showed a clear benefit of physical rotation cues only for simple spatial task (Bakker et al, 1999;Klatzky et al, 1998;Lathrop & Kaiser, 2002;Pausch et al, 1997), but not for more complex navigation tasks Ruddle & Lessels, 2006, the current study provides first evidence that allowing VR users control simulated rotations with their own body can have significant benefits over mere joystick navigation. Moreover, navigation performance in this real-turn mode was statistically equivalent to performance for actual walking in six out of eight dependent variables, and the real-turn mode even reduced the amount of viewing direction changes significantly.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Whereas previous studies showed a clear benefit of physical rotation cues only for simple spatial task (Bakker et al, 1999;Klatzky et al, 1998;Lathrop & Kaiser, 2002;Pausch et al, 1997), but not for more complex navigation tasks Ruddle & Lessels, 2006, the current study provides first evidence that allowing VR users control simulated rotations with their own body can have significant benefits over mere joystick navigation. Moreover, navigation performance in this real-turn mode was statistically equivalent to performance for actual walking in six out of eight dependent variables, and the real-turn mode even reduced the amount of viewing direction changes significantly.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies suggest that adding physical rotations cues can improve spatial orientation performance compared to visual-only simulations for various basic spatial tasks (Bakker, Werkhoven, & Passenier, 1999;Klatzky et al, 1998;Lathrop & Kaiser, 2002;Pausch et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, virtual environments that include self-locomotion (Bakker, Werkhoven, & Passenier, 1999;May & Klatzky, 2000;May, Wartenberg, & Peruch, 1997;Steck, Mochnatzky, & Mallot, 2003) or passive reception of movement (Christou & Bülthoff, 2000;Foreman & Wilson, 1996;Höll, Leplow, Schönfeld, & Mehdorn, 2003;Kirschen, Kahana, Sekuler, & Burack, 2000;Mallot, Gillner, van Venn, & Bülthoff, 1998;Nadel et al, 1998;Péruch & Gaunet, 1998;Waller, Beall, & Loomis, 2004) provide sufficient information for spatial orientation. Yet, it remains unclear whether a further reduction of the sensory input by means of a simple computer-based simulation is sufficient to allow for accurate spatial orientation.…”
Section: Frames Of Reference In Spatial Orientationmentioning
confidence: 99%
“…Virtual environments can be more complex than natural environments with respect to their scale [4,2], structural complexity and dimensionality [5]. Furthermore, virtual environments often differ from natural environments with respect to the sensory modalities involved, depending on the use of visual, auditory and vestibular displays [6,7,8,9,10,11] and interaction methods [8]. Thus, an optimal support of human spatial navigation in virtual environments relies on knowing the effects of involving multiple sensory modalities.…”
Section: Introductionmentioning
confidence: 99%